1996
DOI: 10.1089/jir.1996.16.127
|View full text |Cite
|
Sign up to set email alerts
|

Regulation and Characterization of the Interferon-α Present in Patients with Advanced Human Immunodeficiency Virus Type 1 Disease

Abstract: To examine a possible association between plasma viremia and interferon-alpha (IFN-alpha) in patients with the acquired immunodeficiency syndrome (AIDS), we performed IFN plasma immunoadsorption by apheresis (IFN-alpha apheresis) in four volunteers with AIDS who had sustained levels of endogenous plasma IFN-alpha. IFN-alpha apheresis with two plasma volume exchanges was performed daily for 5 days. Clinical signs and symptoms and hematologic, virologic, and immunologic parameters were monitored. Two subjects de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…These results agree with those of others who showed that IFN‐α produced by cells from retrovirus‐infected animals has a restricted antiviral activity [15]. In other studies IFN‐α from patients infected with HIV‐1 had a normal antiviral activity [23], which disagrees with our results; the discrepancy between the antiviral activity of IFN in patients in our work and in those of other authors may be due to the nature of the IFN‐α. Indeed, these authors examined endogenous plasma IFN‐α of patients infected with HIV‐1, whereas in the current work we studied IFN‐α produced in vitro by blood cells of patients.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…These results agree with those of others who showed that IFN‐α produced by cells from retrovirus‐infected animals has a restricted antiviral activity [15]. In other studies IFN‐α from patients infected with HIV‐1 had a normal antiviral activity [23], which disagrees with our results; the discrepancy between the antiviral activity of IFN in patients in our work and in those of other authors may be due to the nature of the IFN‐α. Indeed, these authors examined endogenous plasma IFN‐α of patients infected with HIV‐1, whereas in the current work we studied IFN‐α produced in vitro by blood cells of patients.…”
Section: Discussionsupporting
confidence: 73%
“…investigated the IFN‐α activity produced by PBMCs of healthy individuals cocultured with HIV‐1‐infected cells [16] and Swindells et al . examined the antiviral activities of endogenous plasma IFN‐α of patients infected with HIV‐1 [23]. In the first studies the IFN‐α was 20‐fold less active than equal quantities of recombinant IFN‐α2b whereas in the second studies IFN‐α from patients had nearly identical antiviral activities to natural and recombinant IFN‐α.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of circulating IFN-␣ in the serum of some HIVinfected individuals was one of the earliest immune alterations discovered in AIDS [121]; like deficient in vitro production of IFN-␣ by NIPC, the presence of serum IFN was associated with a poor prognosis. Curiously, the circulating IFN-␣ in patients with HIV was found to be sensitive to treatment at pH 2, although none of the individual IFN-␣ subtypes are themselves intrinsically acid-labile; furthermore, Gendelman and colleagues [122] isolated the IFN-␣ from plasma from HIV-infected individuals and found that the purifed IFN-␣ was not acid-labile [123]; instead, a serum factor found in HIV-infected individuals as well as individuals with lupus is able to confer the lability [124,125]. Moreover, although presumed by many to be the pDC, the source of the circulating IFN-␣ has not been described definitively.…”
Section: Evidence Of In Vivo Production Of Ifn-␣ In Hiv Infectionmentioning
confidence: 99%
“…Besides its well-documented potent antiviral properties in vivo and in vitro and the stimulation of the Th-1 response described to be important in HIV-1 resistance (13), early work, pioneered by a Freshly isolated PBMC were incubated in the presence or absence of 300 ng/ml p24 Ag equivalent NL4-3, AT2-treated NL4-3, heat-inactivated (HI) NL4-3, human IFN-␣ (10,000 U/ml), influenza virus strain PR8 (10 HA/ml), resiquimod (10 g/ml), or LPS (100 ng/ml) for 18 h. Gendelman's group and others (8,29,30,69), demonstrated biological differences in IFN-␣ proteins produced during advanced HIV infection compared to those of the controls. A limitation of our study is that the HIV ϩ cohort analyzed does not include patients with opportunistic infections or with end stage disease (i.e., CD4 counts Ͻ 50 copies/ml), which may represent an immunopathogenic situation different from those described in the present study, with steady-state viremia and higher CD4 counts.…”
Section: Downloaded Frommentioning
confidence: 99%